Progress in Dual (Piezoelectric-Magnetostrictive) Phase Magnetoelectric Sintered Composites - Rashed Adnan Islam; Shashank Priya (Advances in Condensed Matter Physics)
The primary aims of this review article are (a) to develop the fundamental understanding of ME behavior in perovskite piezoelectric-spinel magnetostrictive composite systems, (b) to identify the role of composition, microstructural variables, phase transformations, composite geometry, and postsintering heat treatment on ME coefficient, and (c) to synthesize, characterize, and utilize the high ME coefficient composite. The desired range of ME coefficient in the sintered composite is 0.5–1 V/cm⋅Oe. The studies showed that the soft piezoelectric phase quantified by smaller elastic modulus, large grain size of piezoelectric phase (~1 μm), and layered structures yields higher magnitude of ME coefficient. It is also found that postsintering thermal treatment such as annealing and aging alters the magnitude of magnetization providing an increase in the magnitude of ME coefficient. A trilayer composite was synthesized using pressure-assisted sintering with soft phase [0.9 PZT–0.1 PZN] having grain size larger than 1 μm and soft ferromagnetic phase of composition Ni0.8Cu0.2Zn0.2Fe2O4 [NCZF]. The composite showed a high ME coefficient of 412 and 494 mV/cm⋅Oe after sintering and annealing, respectively. Optimized ferrite to PZT thickness ratio was found to be 5.33, providing ME coefficient of 525 mV/cm⋅Oe. The ME coefficient exhibited orientation dependence with respect to applied magnetic field. Multilayering the PZT layer increased the magnitude of ME coefficient to 782 mV/cm⋅Oe. Piezoelectric grain texturing and nanoparticulate assembly techniques were incorporated with the layered geometry. It was found that with moderate texturing, d33 and ME coefficient reached up to 325 pC/N and 878 mV/cm⋅Oe, respectively. Nanoparticulate core shell assembly shows the promise for achieving large ME coefficient in the sintered composites. A systematic relationship between composition, microstructure, geometry, and properties is presented which will lead to development of high-performance magnetoelectric materials.